(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
Language is a critical component of human interaction and societal development, influencing cultural identity, education, economic progress, and social cohesion. This paper examines the multifaceted relationship between language and society, focusing on how language serves as a tool for communication, shapes educational outcomes, impacts economic development, and informs language policy. By analyzing existing literature and case studies, this study highlights the significance of linguistic diversity in fostering inclusive societies